2019
DOI: 10.1111/gbb.12599
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous loss of epilepsy geneKCNQ2alters social, repetitive and exploratory behaviors

Abstract: KCNQ/K v 7 channels conduct voltage-dependent outward potassium currents that potently decrease neuronal excitability. Heterozygous inherited mutations in their principle subunits K v 7.2/KCNQ2 and K v 7.3/KCNQ3 cause benign familial neonatal epilepsy whereas patients with de novo heterozygous K v 7.2 mutations are associated with early-onset epileptic encephalopathy and neurodevelopmental disorders characterized by intellectual disability, developmental delay and autism. However, the role of K v 7.2-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 137 publications
(384 reference statements)
3
48
0
Order By: Relevance
“…However, heterozygous KCNQ2 knock-out mice are viable and display increased locomotor activity and exploratory behavior ( Kim et al, 2020 ), consistent with behavioral hyperactivity induced by transgenic suppression of K v 7 currents ( Peters et al, 2005 ) and amphetamine and XE991 ( Sotty et al, 2009 ). These mice also show decreased sociability and increased repetitive and compulsive behavior ( Kim et al, 2020 ), reminiscent of autism seen in some EE patients with dominant KCNQ2 mutations ( Weckhuysen et al, 2012 , 2013 ; Milh et al, 2013 ). However, the precise circuitries responsible for these abnormal behaviors remain unknown.…”
Section: Role Of K V 7 Channels In Hippocampus-depmentioning
confidence: 80%
See 1 more Smart Citation
“…However, heterozygous KCNQ2 knock-out mice are viable and display increased locomotor activity and exploratory behavior ( Kim et al, 2020 ), consistent with behavioral hyperactivity induced by transgenic suppression of K v 7 currents ( Peters et al, 2005 ) and amphetamine and XE991 ( Sotty et al, 2009 ). These mice also show decreased sociability and increased repetitive and compulsive behavior ( Kim et al, 2020 ), reminiscent of autism seen in some EE patients with dominant KCNQ2 mutations ( Weckhuysen et al, 2012 , 2013 ; Milh et al, 2013 ). However, the precise circuitries responsible for these abnormal behaviors remain unknown.…”
Section: Role Of K V 7 Channels In Hippocampus-depmentioning
confidence: 80%
“…Behavioral phenotyping of the global or conditional homozygous KCNQ2 knock-out mice has not been possible due to their early postnatal lethality or premature death, respectively (Watanabe et al, 2000;Soh et al, 2014). However, heterozygous KCNQ2 knock-out mice are viable and display increased locomotor activity and exploratory behavior (Kim et al, 2020), consistent with behavioral hyperactivity induced by transgenic suppression of K v 7 currents (Peters et al, 2005) and amphetamine and XE991 (Sotty et al, 2009). These mice also show decreased sociability and increased repetitive and compulsive behavior (Kim et al, 2020), reminiscent of autism seen in some EE patients with dominant KCNQ2 mutations (Weckhuysen et al, 2012(Weckhuysen et al, , 2013Milh et al, 2013).…”
Section: Role Of K V 7 Channels In Hippocampus-dependent Learning Andmentioning
confidence: 99%
“…The focus of these earlier studies was mainly on seizure susceptibility, as Kv7.2 was not linked yet to behavioral abnormalities. With the current evidence that the Kv7.2 channel plays a role in neurodevelopment and that variants in KCNQ2 are enriched in ASD cohorts, the KCNQ2 KO model was also subjected to extensive behavioral analysis; an in-depth behavioral study, indeed, recently showed autismassociated behaviors such as a decrease in social behavior and enhanced repetitive behaviors in KCNQ2 heterozygous KO mice (Kim et al, 2020).…”
Section: Kcnq2 Ko Mouse Modelsmentioning
confidence: 99%
“…The role of Kv7.2 dysfunction in the expression of abnormal GABAergic parvalbumin-positive interneurons and their dendritic arborization within corticostriatal and nigrostriatal dopaminergic transmission (an impairment also described in Mecp2-null mice) could suggest a possible link between Rett syndrome, KCNQ2 encephalopathy, and other neuropsychiatric disorders in terms of the pathophysiology of hypokinetic movement disorders, dystonia, and hand stereotypies. 7 Recent experimental data on KCNQ2+/− mice established a link between loss-of-function Kv7.2 mutations and behavioral disorders that was characterized by increased repetitive and compulsive behaviors, reduced social interest, and impaired social interaction mechanisms. 7 …”
mentioning
confidence: 99%
“… 7 Recent experimental data on KCNQ2+/− mice established a link between loss-of-function Kv7.2 mutations and behavioral disorders that was characterized by increased repetitive and compulsive behaviors, reduced social interest, and impaired social interaction mechanisms. 7 …”
mentioning
confidence: 99%